Electronically monitored medication adherence in idiopathic pulmonary fibrosis: prevalence, predictors and outcomes. Issue 3 (1st August 2022) - Delameillieure, Anouk; Wuyts, Wim A.; Pironet, Antoine; Dobbels, Fabienne
Medication adherence studies in idiopathic pulmonary fibrosis (IPF) are limited, use cross-sectional designs and report discontinuation rates. We prospectively investigated adherence to pirfenidone in IPF patients using electronic monitoring, which provides insights on whether and when the medication was taken on a day-by-day basis. We investigated the impact of nonadherence on lung function and selected predictors for nonadherence based on the COM-B behavioural model. The longitudinal statistical analyses included generalised estimation equations and linear mixed effects models. 55 patients initiating pirfenidone were followed-up for 2 years after diagnosis (76.4% men, mean age 71.1 years (range 50–87 years), mean forced vital capacity (FVC) 88% predicted (sd 18.3), mean diffusing capacity of the lung for carbon monoxide ( D LCO ) 58.1% predicted (sd 14.7)). Our data showed an association (p=0.03) between the proportion of days with three pirfenidone intakes ( i.e. dosing adherence) and FVC % predicted, whereby a high dosing adherence seemed necessary to maintain stable or improving FVC % predicted values. 58.2% of the participants were able to implement at least 90% correct dosing days, yet adherence significantly decreased over time. Too short dosing intervals had negative effects on lung function outcomes. Knowledge on IPF and self-reported adherence were significantly associated with electronically measured adherence. In conclusion, nonadherence is prevalent and might negatively affect lung function. Further research is needed on the impact of nonadherence on outcomes and its predictors, so that tailored interventions can be developed. Meanwhile, a self-report questionnaire could be used to identify adherence issues and teams should equip patients with knowledge about their treatment and how to take it. This study used electronic monitoring systems for the first time in IPF patients to assess taking and timing of pirfenidone. Medication nonadherence is a prevalent issue that increases over time and is associated with patients' lung function outcomes. https://bit.ly/3wEFUlq